2013
DOI: 10.1007/s10067-013-2357-5
|View full text |Cite
|
Sign up to set email alerts
|

Consultations with complementary and alternative medicine practitioners amongst wider care options for back pain: a study of a nationally representative sample of 1,310 Australian women aged 60–65 years

Abstract: Back pain is a significant health service issue in Australia and internationally. Back pain sufferers can draw upon a range of health care providers including complementary and alternative medicine (CAM) practitioners. Women are higher users of health services than men and tend to use CAM frequently for musculoskeletal conditions. However, there remain important gaps in our understanding of women's consultation patterns with CAM practitioners for back pain. The objective of this study is to examine the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…The majority of large sample-sized population studies were from North America (n58) and Australia (n57), and Australia had the largest number of large-sized population studies specific to back pain (n56). Of these Australian back pain-focused studies, five articles reported analyses from a National Longitudinal Study on Women's Health [26,47,50,58,59]. The analysis of the articles has been grouped into five themes, and Table 5 provides an overview of the important findings.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The majority of large sample-sized population studies were from North America (n58) and Australia (n57), and Australia had the largest number of large-sized population studies specific to back pain (n56). Of these Australian back pain-focused studies, five articles reported analyses from a National Longitudinal Study on Women's Health [26,47,50,58,59]. The analysis of the articles has been grouped into five themes, and Table 5 provides an overview of the important findings.…”
Section: Resultsmentioning
confidence: 98%
“…Only four studies had small sample sizes and were conducted in clinical settings [60,61,66,67]. Of the large sample-sized studies, 8 were conducted in clinical settings [30,43,[62][63][64][65]68,69] and the remaining 18 were population-based studies [26,29,42,44,45,[47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations